Code : the hidden language of computer hardware and software - Petzold, Charles, 1953- (Redmond (Wash.) : Microsoft press, 2023)
Computers are everywhere - most obviously in our laptops and smartphones, but also our cars, televisions, microwave ovens, alarm clocks, robot vacuum cleaners, and other smart appliances. Have you ever wondered what goes on inside thes devices to make our lives easier but occasionally more infuriating? For more than 20 years, readers heave delighted in Charles Petzold's illuminating story of the secret inner life of computers, and now he has revised it for this new age of computing. Cleverly illustrated and easy to understand, this is the book that cracks the mystery. You'll discover what flashlights, black cats, seesaws, and the ride of Paul Revere can teach you about computing - and how human ingenuity and our complusion tot communicate have shaped every electronic device we use. This new expanded edition explores more deeply the bit-by-bit, gate-by-gate construction of the heart of every smart device - the central processing unit that combines the simplest of basic operations to perform the most complex of feats. Along with new chapters, Petzold has created a new website, CodeHiddenLanguage.com, that uses animated interactive graphics to make computers even easier to comprehend. Form the simple ticking of clocks tot the worldwide hum of the internet, Code reveals the essence of the digital revolution.
Keywords: Digitale revolutie